Geochemical Characteristics of the Bituminous Carbonate and Shale Rocks of the Jurassic Sequences (Sargelu, Naokelekan and Chia Gara) in the North Thrust Zone, North of Zakho, North of Iraq - Al-Jaafary, Amjed; Hadi, Ayten (Iraqi Journal of Science, 2025)
The geochemistry and mineralogy of the three formations ; Sargelu, Naokelekan and Chia Gara are studied using XRF, XRD, SEM, and EDS-elemental map analyses. These formations represent Jurassic sequences exposed to the North of Zakho within the North Thrust Zone, and constitute bituminous carbonate and shale rocks. The average concentrations of SiO2 and CaO in carbonate rocks are (11.7%, 7.75% and 9.16%) and (32.40%, 27.51% and 46.73%) in Sargelu, Naokelekan and Chia Gara Formations respectively, whereas in shale rocks are (27.51% and 19.48%) and (7.09% and 4.60%) in Sargelu and Naokelekan Formations. The MgO content as average in carbonate rocks is high in Sargelu (8.86%) compared to Naokelekan (0.28%) and Chia Gara (0.22%). The average contents of V, Ni, Mo and Zn in carbonate rocks are (143.2 ppm, 94.92 ppm, 96.95 ppm and 83.3 ppm) in Sargelu, (1143.3 ppm, 619.8 ppm, 588.3 ppm and 942.5 ppm) in Naokelekan and (373.4 ppm, 92 ppm, 187.4 ppm and 35.2 ppm) in Chia Gara, while in shale rocks are (661.99 ppm, 662.6 ppm, 832.8 ppm and 509 ppm) in Sargelu and (1990.8 ppm, 753.1 ppm, 324.7 ppm and 724.3 ppm) in Naokelekan.The concentrations and geochemical relationships of the major oxides are more or less similar in both types of rocks in the three formations but their relationships with trace elements are diverse. These relationships are very compatible with the mineralogical identification. SiO2, Al2O3, K2O, TiO2 and Zr make positive correlations with each other reflecting their existence in clay minerals, K-feldspars and are of detrital origin. CaO shows negative correlation with these oxides indicating different origin. Also CaO is related with PO4 infers the presence of apatite. Fe2O3, SO3, Mo, Zn, Ni and Cd are correlated positively due to their co-existence in sulfide minerals.The distributions of the trace elements Zn, Ni, Cu, Cr, Cd, V and Mo are controlled by the clay minerals, oxides, phosphates, sulfides and sulfates. Mn, As, Sr and Ba distributions are mainly controlled by carbonate minerals (calcite, dolomite) and barite.